Pola-Pola Sosialisasi Perbankan Syariah Melalui Masjid - Soritua Ahmad Ramdani Harahap; Dadang Irsyamuddin; Muhammad Ulul Azmi (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2020)
Islamic banking is a banking that holds firm commitments to the principles of sharia in all its activities. However, there are still many people who think that there is no difference between the Islamic banking and conventional banking. This study aims to determine the pattern of sharia banking socialization through mosques in Jogyakarta. This study used qualitative research methods. The results of this study indicate that the mosque is a good place to explain the understanding of Islamic economics, especially the use of Islamic banking to the public. This is because the mosque is the main center of worship for all Muslims. In addition, it is necessary to have innovations and creations from academics and practitioners to jointly introduce Islamic banking to the public through ways that are easily accepted by the public so that the public has a good understanding and understanding of the nature of Islamic economics and the use of Islamic banking.